Effects of Digital Badges on the Online Activity of University Students in a Blended Learning Model - Gonzales López, Eduardo Fabio (2019)
This research aimed to determine the effects a digital badge program had on the academic performance and participation in online activities in the English I course. The research design was experimental with post-test and control group. The sample consisted of 18 students from the first semester, enrolled in a blended learning model in a private university in Lima. There were statistically significant differences between the control and experimental group, which favored the experimental group. In addition, an effect size of 4.56 was found, which was considered very large. Regarding academic performance, no statistically significant differences were found. However, the effect size was 0.60, considered moderate. In conclusion, the digital badge program encouraged participation in virtual academic activities; however, the results obtained in connection with academic performance are not entirely clear, which is why it is suggested to conduct research in courses of different areas, with a broader sample.